The Distinction between Law and Gospel in its Significance for Political Theology: Systematic Considerations - Deinhammer, Robert (LPPM - Sekolah Tinggi Teologi Indonesia Jakarta, 2025)
This paper explores the theological distinction between Law and Gospel and its critical relevance for Political Theology. In contemporary debates, religion's role in shaping morality and politics is increasingly contested—secularists often view faith-based ethics as irrational or even harmful, while theologians argue that secularism itself may function ideologically. Within this tension, the study aims to clarify the relationship between faith, morality, and political power through a systematic reappraisal of the Law-Gospel distinction. Drawing primarily from Lutheran theology and engaging with Catholic perspectives, the author outlines how the Law—seen as God’s normative will—demands moral behavior and structures just political order, while the Gospel—God’s unconditional grace—empowers believers to fulfill the Law through love and trust, overcoming fear and self-interest. This theological lens is then applied to evaluate secular and religious political ideologies, arguing that the Law-Gospel dynamic provides a critical and liberating framework for Political Theology. The results highlight how distinguishing without separating Law and Gospel fosters a prophetic theology that both grounds normative ethics and upholds the transformative power of grace. The study contributes to Political Theology by offering a model that avoids legalism and moralism, while remaining ethically rigorous and theologically grounded, capable of engaging both secular reasoning and Christian faith in public discourse.